A two-step process for the synthesis of sweetening syrup from aqueous lactose. (January 2020) - Cheng, Shouyun; Hummel, Matt; Dahal, Bishnu; Gu, Zhengrong; Kharel, Parashu; Martínez-Monteagudo, Sergio I.
Abstract: Dairy industry continues to struggle in finding new uses for lactose. In this work, a two-step process was developed for the synthesis of sweetening syrup from aqueous lactose. The process consisted of enzymatic hydrolysis (β-galactosidase) followed by catalytic isomerization over tin in the framework of dealuminated beta zeolite (Sn/deAlβ). The enzymatic hydrolysis was studied within a wide range of enzyme concentration (1–6%), lactose concentration (5–45%), and hydrolysis time (1–24 h). Under optimized conditions of the enzymatic hydrolysis, 95.77 ± 0.67% of lactose was converted into glucose and galactose after 1 h of hydrolysis. In the second step, the hydrolysed lactose was catalytically isomerized at 100 °C for 2 h in the presence of Sn/deAlβ containing different Sn loading ratios (2–8 wt%). The prepared catalysts were characterized by BET, XRD, FTIR, CO2 -TPD, and TEM. The highest isomerization yield of glucose and galactose to produce fructose andd -tagatose (29.8 ± 0.5 and 25.5 ± 0.5%, respectively) was obtained with 6% of Sn/deAlβ. The overall process converted 99.9% of lactose into a sweetening syrup principally made of glucose (24%), galactose (13%), fructose (14%), andd -Tagatose (12%). Importantly, this work highlights the production of a sweetening syrup from aqueous lactose by applying a two-step process. Highlights: A two-step process for the production of a sweetening syrup was developed. 99.9% of the lactose was converted into a sweetening syrup. The isomerization yield of fructose andd -Tagatose was 29.8 ± 0.5 and 25.5 ± 0.5%, respectively. Sn/deAlβ with different Sn loadings were used for the catalytic isomerization.